2015
DOI: 10.7453/gahmj.2015.080
|View full text |Cite
|
Sign up to set email alerts
|

Resilient Warrior: A Stress Management Group to Improve Psychological Health in Service Members

Abstract: Background:Many veterans deployed after 9/11/2001 are impacted by subthreshold levels of posttraumatic stress, anxiety, or other psychological health problems that may interfere with successful reintegration. Conventional treatments, including medication and trauma-focused individual psychotherapies, may not be optimally adapted, accepted, or effective to treat these subsyndromal symptoms.Methods:We developed “Resilient Warrior,” a 4-session, group-based, mind-body stress-management and resilience program targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Studies recruited soldiers recently returning from deployment [ 35 , 36 ], veterans of Iraq or Afghanistan [ 37 42 ], Reservists [ 43 , 44 , 45 ] and a combination of veterans and currently serving soldiers [ 39 , 46 ]. The majority of participants were male, with a mean age of between 18 and 37 years [ 35 38 , 40 , 42 45 ]. Two studies recruited a cohort whose mean age was between 42 and 45 years [ 41 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies recruited soldiers recently returning from deployment [ 35 , 36 ], veterans of Iraq or Afghanistan [ 37 42 ], Reservists [ 43 , 44 , 45 ] and a combination of veterans and currently serving soldiers [ 39 , 46 ]. The majority of participants were male, with a mean age of between 18 and 37 years [ 35 38 , 40 , 42 45 ]. Two studies recruited a cohort whose mean age was between 42 and 45 years [ 41 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the effectiveness of interventions both individual and relationship level outcomes were reported. Studies examined the effectiveness of facilitated group interventions [ 38 , 41 , 43 , 45 ], self-directed interventions using multi-media and online formats [ 39 , 40 , 44 ], and one study evaluated an intervention administered one-to-one by a clinician [ 37 ]. The characteristics of studies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A short 4-session intervention incorporating mindfulness in the mind-body approach, modestly increased resilience and also decreased depressive and anxiety symptoms and perceived stress in veterans though only assessed post-intervention [61]. These effects translate to improvements in quality of life [62] with a reduction in somatic symptoms including dizziness, fatigue and tension in addition to depressive symptoms as shown in veterans with PTSD [63].…”
Section: Mindfulnessmentioning
confidence: 99%
“…The SMART- 3RP (Relaxation Response and Resilience Programme) teaches self-care strategies to protect against the negative effects of stress and improve coping skills (Park et al 2013). This programme has been used with various populations, including members of the US armed services, older adults, and adults with chronic physical illness, to help manage symptoms of depression, anxiety and PTSD (Sylvia et al 2015; Scult et al 2015; Vranceanu et al 2014). The programme also had positive effects with professionals working in stressful medical professions, including palliative care clinicians and interpreters in cancer care (Mehta et al 2016; Park et al 2016).…”
Section: Introductionmentioning
confidence: 99%